Experimental and numerical analyses of the hysteretic performance of an arched aluminium alloy gusset joint. (February 2022) - Wu, Jinzhi; Li, Yuhang; Sun, Guojun; Chen, Song
Abstract: An aluminium alloy gusset joint with a 7° arch is designed and fabricated, and a cyclic loading test is carried out to address the research gap regarding the hysteretic performance of arched aluminium alloy gusset joints. The mechanical behaviour and the failure mode of the joint under a cyclic load are obtained, and the failure mechanism is explained. The hysteresis, skeleton, and stiffness degradation curves are plotted and discussed, the ductility coefficient is calculated, and the stress–strain behaviour is analysed in detail. The experimental results show that the member webs in the joint zone exhibit local buckling under a cyclic load. The row of bolts on the upper flange closest to the edge of the node plate is torn when the joint is loaded upward. A 1/4 symmetry model is established using the ABAQUS finite element (FE) software. The effectiveness of the FE simulation method and the validity of the model are verified by experiments. Furthermore, a 0° and 5° aluminium alloy gusset joint models are established to investigate the properties of the aluminium alloy gusset joint with different arched angles. It is shown that the 0° joint has lower ultimate bearing capacity and higher energy dissipation capacity and ductility than 5° and 7° joints. In addition, the failure modes of three joints have been studied, providing a reference for the seismic design of aluminium alloy structures. Highlights: Based on actual engineering, an arched aluminium alloy gusset joint model is designed. The failure mode and mechanical behaviour of aluminium alloy gusset joint under a cyclic load are analysed experimentally. The hysteretic performance of the arched aluminium alloy gusset joint is obtained experimentally. Variation law of stress and strain of joint under cyclic loading is provided. The influence of the arch on the bearing capacity and hysteretic performance of the joint are determined.